The COVID-19 coronavirus outbreak: a current view - Temte, Jonathan (Henry Stewart Talks, 2020)
Is Covid-19 a greater challenge than other coronavirus strains?, Possible scenarios for the spread of the virus, Strategies that countries worldwide should consider, Implications of the outbreak for future global health and health strategies